2013
DOI: 10.1002/etc.2192
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability‐based chronic toxicity measurements of permethrin to Chironomus dilutus

Abstract: Compared with acute toxicity, chronic exposures to low levels of contaminants are more environmentally relevant, but fewer data are available. In the present study, sediment toxicity of the pyrethoid permethrin to Chironomus dilutus was determined. The whole-life-cycle toxicity testing was conducted with the endpoints covering survival, growth, emergence, and reproduction. Permethrin caused 50% lethality in C. dilutus at 1.83 ± 1.13 µg/g organic carbon (OC) and 1.20 ± 0.55 µg/g OC after exposures of 20 d (befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…2B) also signify remarkable environmental risks. Sediment samples reflect exposure conditions over longer time spans compared with those of water samples, and the high exceedance levels (i) support the data reported for water, (ii) are likely due to the high hydrophobicity of many insecticides, (iii) imply long-term (chronic) risks to sediment-dwelling organisms (23), and (iv) indicate that both major aquatic ecosystem components are at risk.…”
Section: Resultssupporting
confidence: 70%
“…2B) also signify remarkable environmental risks. Sediment samples reflect exposure conditions over longer time spans compared with those of water samples, and the high exceedance levels (i) support the data reported for water, (ii) are likely due to the high hydrophobicity of many insecticides, (iii) imply long-term (chronic) risks to sediment-dwelling organisms (23), and (iv) indicate that both major aquatic ecosystem components are at risk.…”
Section: Resultssupporting
confidence: 70%
“…Meanwhile, a control sediment was collected from a drinking-water reservoir in Conghua, China. This sediment exhibited no chronic toxicity to the midges and contained no target contaminants at concentrations greater than the reporting limits (RLs) (Du et al 2013(Du et al , 2014.…”
Section: Sediment Collection and Acute-toxicity Testingmentioning
confidence: 99%
“…Life-cycle toxicity tests using C. dilutus were performed in triplicate for each group according to a previously published method (Du et al 2013). In brief, the test was initiated from newly hatched midge larvae (\24 h old) and terminated on the hatch of the second generation.…”
Section: Chronic-toxicity Testsmentioning
confidence: 99%
“…Sediment samples were sieved through a 2-mm sieve on site and transported to Guangzhou Institute of Geochemistry, Chinese Academy of Sciences (GIGCAS), where they were sieved through a 500-lm sieve, homogenized, and stored at 4°C. Previous toxicity testing and analytical work showed that the control sediment had limited contamination and did not exhibit adverse effects to benthic organisms (Du et al 2013). After inorganic carbon was removed by 1 mol/l HCl solution, total OC content of the sediment was analyzed using an Elementar Vario EL III elemental analyzer (Hanau, Germany) with a value of 1.60 ± 0.14 %.…”
Section: Sediment Spikingmentioning
confidence: 99%
“…Three replicates were used for each group. Specific end points used are listed in Table 2, and the evaluation of toxic end points followed the methods reported in our previous study (Du et al 2013). …”
Section: Bioassaysmentioning
confidence: 99%